Effective use of activated potassium salt of long chain phosphorous (96%) for the control of fungicide resistant Plasmopara viticola causing downy mildew in grapes - INDU S. SAWANT and SUJOY SAHA*, S.D. SAWANT, M.R. GHULE, R.M. SAVARDEKAR (Indian Phytopathology, 2016)
Grape is one of the important commercial fruit crops of India and is severely affected by downy mildew disease caused by Plasmopara viticola which might cause total crop loss under favourable conditions. Synthetic fungicides belonging to groups Quinone outside Inhibitors (QoI), Carboxylic Acid Amides (CAA), phenyl amides (PA), Cyanoacetamide-oxime, are commonly used for the control of downy mildew in India, alone or in combination with non systemic fungicides viz. dithiocarbamates, and copper based fungicides. P. viticola is high risk pathogen for its ability to develop resistance against fungicides. Resistance to QoI, CAA, and phenyl amide group fungicides were detected in India and other vineyards of various countries. Therefore it is necessary to strategize alternative safe methods for disease control. A commercial formulation containing activated potassium salt of long chain phosphorous 96% (APSP 96%), was evaluated in vitro against fungicide resistant isolates of P. viticola and in field during the fruiting season of October to April 2014-15 at Nashik and Sangli locations in Maharashtra against downy mildew. It was found that the APSP 96% used solo and when tank-mixed with mancozeb, significantly reduced downy mildew incidence on leaves and bunches in grapes as compared to untreated control and can be safely used in vineyards to prevent the buildup of fungicide resistant population and effective disease management.